HUBUNGAN MANUSIA DAN TEKNOLOGI DALAM TINJAUAN FILSAFAT TEKNOLOGI DON IHDE (Studi Film Say Hello To Yellow Karya BW Purba Negara) - Rufus Goang Swaradesy (LAYAR: Jurnal Ilmiah Seni Media Rekam, 2021)
The short film titled Say hello to Yellow by B. W. Purba Negara is one of the films that raises the relationship of technology in human life. there is a connection between the human,world, and technology. The perceiving of human to the world is evident in the scenes in the movie Say hello to Yellow. This paper is a descriptive qualitative. The main data source is a short film titled Say hello to Yellow by B. W. Purba Negara. The analysis knife used is Don Ihde's technological philosophy theory about human relationship with technology. The results of this study showed that in the film Say Hello to Yellow there are characters (risma friends) who are able to maintain their existence as human beings and there are characters (Risma) whose existence as a human being is affected by the existence of technology.